Prediction the widths of maxillary and mandibular canines and premolars from the widths of maxillary incisors and first molars (Iraqi study) - Mohammed Nahidh (Journal of Baghdad College of Dentistry, 2013)
Background: This study aimed to use the combined mesio-distal crowns widths of maxillary incisors and first molars as predictors to the combined mesio-distal crowns widths of maxillary and mandibular canines and premolars. Materials and methods: The sample included 110 Iraqi Arab subjects with an age ranged between 17-25 years and class I skeletal and dental relations. The crown widths of maxillary teeth and mandibular canines and premolars were measured at the largest mesio-distal dimension on the study casts using digital electronic caliper with 0.01 mm sensitivity. Pearson’s correlation coefficient was used to determine the relation between the combined mesio-distal crowns widths of maxillary incisors and first molars and the combined mesio-distal crowns widths of maxillary and mandibular canines and premolars. Regression analysis was used to determine the equations that predict the widths of maxillary and mandibular canines and premolars. Paired sample t-test was used to compare between the actual and predicted mesio-distal crown widths. Results and Conclusions: The findings showed a non-significant difference between the predicted and actual mesio-distal crown widths; hence the combined mesio-distal widths of maxillary incisors and first molars can be used as predictors for the combined mesio-distal widths of maxillary and mandibular canines and premolars.